If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(4x+3)+8=5x-8(2-6x)-9x
We move all terms to the left:
8(4x+3)+8-(5x-8(2-6x)-9x)=0
We add all the numbers together, and all the variables
8(4x+3)-(5x-8(-6x+2)-9x)+8=0
We multiply parentheses
32x-(5x-8(-6x+2)-9x)+24+8=0
We calculate terms in parentheses: -(5x-8(-6x+2)-9x), so:We add all the numbers together, and all the variables
5x-8(-6x+2)-9x
We add all the numbers together, and all the variables
-4x-8(-6x+2)
We multiply parentheses
-4x+48x-16
We add all the numbers together, and all the variables
44x-16
Back to the equation:
-(44x-16)
32x-(44x-16)+32=0
We get rid of parentheses
32x-44x+16+32=0
We add all the numbers together, and all the variables
-12x+48=0
We move all terms containing x to the left, all other terms to the right
-12x=-48
x=-48/-12
x=+4
| 81=3+6n | | (3x-6)+(3x-6)=36 | | (7x+1/2=)+(5x-81/2=) | | 3j+2=15 | | w/7+26=34 | | 2/9y+21=11 | | 60=-5{x-6} | | 4-(2x+1)=6-4x | | -7s+11=-80 | | 2x+4.5=2.5 | | 3y=19.8 | | –5+w=2w | | 6.40x+4.80=11.65 | | 9f+5=3f-7 | | -15=-3/5u | | -7=21-x/4 | | b+2.02=5.5 | | z=49-53/13.4 | | -6(x-3)=2(2x+4)-5x | | 5e/12-8=44 | | f+12/4=5 | | -3x^2-36x+9=0 | | -4{x-4}=44 | | z=49-43/13.4 | | –50u2=2 | | 21}8n-5=139 | | -5/9y=10 | | 4x+4=198 | | z-12=3z-40 | | 17=4u+1 | | 10–2x=–6+6x | | 3(x-4)=12x+15 |